1998
DOI: 10.1046/j.1469-0705.1998.12020097.x
|View full text |Cite
|
Sign up to set email alerts
|

Second‐trimester measurements of placental volume by three‐dimensional ultrasound to predict small‐for‐gestational‐age infants

Abstract: Three-dimensional sonographic measurement of the placental volume alone is not a satisfactory technique for predicting SGA infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
82
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 0 publications
7
82
0
4
Order By: Relevance
“…Moreover, our method was only verified by comparing 2-D to 3-D estimated volumetry datasets. Ultrasound estimations tend to have an inaccuracy of ±10-20%.The estimated placental volumes based on our model correlated significantly to the actual estimated fetal weight which corresponds to the studies stating strong correlation between placental and fetal weight both in the first and second trimester and at the delivery as well (Thame et al 2001;Derwig et al 2011;Hafner et al 1998;Almog et al 2011). …”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Moreover, our method was only verified by comparing 2-D to 3-D estimated volumetry datasets. Ultrasound estimations tend to have an inaccuracy of ±10-20%.The estimated placental volumes based on our model correlated significantly to the actual estimated fetal weight which corresponds to the studies stating strong correlation between placental and fetal weight both in the first and second trimester and at the delivery as well (Thame et al 2001;Derwig et al 2011;Hafner et al 1998;Almog et al 2011). …”
Section: Discussionsupporting
confidence: 82%
“…Salafia et al (2006) suggested that large placenta relative to the fetal weight might represent placental insufficiency with reduced ability to maintain fetal growth. Thus, sonographic estimation of the placental growth in addition to the fetal growth is an important perinatal predictive indicator (Gassner et al 2003;Hafner et al 1998;Odibo et al 2011;Salafia et al 2006;Thame et al 2001;Thame et al 2004) and might be an adjunct modality of uteroplacental flow (Rotmensch et al 1994). These facts underline the necessity of routine placental volumetry in everyday practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With improved 3-dimensional (3D) sonographic technology, it is now possible to evaluate the placental volume as well as vascularization status using power Doppler sonography. [1][2][3][4][5][6] The Doppler parameters derived from 3D interrogation are different from those using conventional sonography and include the vascularization index (VI), flow index (FI), and vascularization-flow index (VFI). [2][3][4] These indices have been reliably measured in the placenta and other gynecologic organs.…”
mentioning
confidence: 99%